2018
DOI: 10.1002/cctc.201801414
|View full text |Cite
|
Sign up to set email alerts
|

Modified Nanocarbons for Catalysis

Abstract: Nanocarbons represent useful scaffolds in the preparation of last generation nanostructured catalysts, and their chemical functionalization through covalent or non‐covalent modification is becoming an important tool for introducing well‐distributed anchoring points and, in the meantime, could be the first step toward the assembling of hybrid nanostructured materials with a hierarchical order. In this Review are reported synthesis and catalytic applications of chemically modified nanocarbons such as fullerene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 345 publications
(254 reference statements)
1
39
0
Order By: Relevance
“…By virtue of their structure, CNHs are very intriguing materials that share some features and chemistry resembling both that of fullerenes, due to the presence of the closed tips, and that of single‐walled CNTs, thanks to their elongated shape. Among the possible applications of CNFs, catalysis is one of the most interesting emerging fields . In this context, transition metals catalyzed C‐C coupling reactions play a central role both in academia and for synthesis of fine chemicals and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of their structure, CNHs are very intriguing materials that share some features and chemistry resembling both that of fullerenes, due to the presence of the closed tips, and that of single‐walled CNTs, thanks to their elongated shape. Among the possible applications of CNFs, catalysis is one of the most interesting emerging fields . In this context, transition metals catalyzed C‐C coupling reactions play a central role both in academia and for synthesis of fine chemicals and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…[84][85][86][87][88]. In recent years, CNFs emerged as suitable support for heterogeneous catalytic materials, due to their high chemical inertness, thermal stability, and mechanical resistance, along with an unconventional lightness [89]. In addition, CNFs are nanoobjects with well-defined structure and dimensions often displaying sharp size distribution, which allows for a homogeneous dispersion of the functionalities and active sites all over their surface, giving rise to reproducible properties.…”
Section: Nanocarbon-based Catalysts For Co 2 Conversion Into Cyclic Cmentioning
confidence: 99%
“…The physicochemical properties of carbon materials can be changed by functionalization or by doping them with heteroatoms such as nitrogen, sulfur, boron and phosphorous. [21][22][23][24] In the last decade, nitrogen-doped carbon and nitrogen-functionalized materials have become an exciting topic in catalysis due to the possibility of explored new metalfree catalytic processes and new catalyst supports. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] As example, it has been reported that nitrogen atoms in a carbon matrix can increase the interaction between metal nanoparticles and the support, change the electronic properties of the support and finally modifying the adsorption energies of the reactants and products.…”
Section: Introductionmentioning
confidence: 99%